2001
DOI: 10.1161/hh0701.088512
|View full text |Cite
|
Sign up to set email alerts
|

Induction of JAB/SOCS-1/SSI-1 and CIS3/SOCS-3/SSI-3 Is Involved in gp130 Resistance in Cardiovascular System in Rat Treated With Cardiotrophin-1 In Vivo

Abstract: Abstract-CIS (cytokine-inducible SH2 protein), SOCS (suppressor of cytokine signaling), or SSI (signal transducers and activators of transcription [STAT]-induced STAT inhibitor) proteins are a family of cytokine-inducible negative regulators of cytokine signaling via Janus kinase (JAK)-STAT pathways. Given the evidence that the JAK-STAT pathway plays a critical role in the cardiovascular system, the primary objective of this study was to assess the effects of the CIS family on JAK-STAT signaling in the cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 39 publications
3
21
0
1
Order By: Relevance
“…Treatment with human rG-CSF resulted in a dramatic increase of SOCS-3 mRNA within 45 min. This rapid induction of SOCS-3 was similar to that observed with other cytokines (47)(48)(49) and this indicates that SOCS-3 is an immediate early gene induced by G-CSF to rapidly modulate G-CSFR-mediated signaling. The strong and rapid induction of SOCS-3 mRNA in myeloid cells by G-CSF reported in this study, together with the previously reported potent induction of SOCS-3 by G-CSF, GM-CSF, and IL-3 in bone marrow cells (22), is a strong indication for SOCS-3 being an important regulator of signal transduction in immune cells.…”
Section: Discussionsupporting
confidence: 82%
“…Treatment with human rG-CSF resulted in a dramatic increase of SOCS-3 mRNA within 45 min. This rapid induction of SOCS-3 was similar to that observed with other cytokines (47)(48)(49) and this indicates that SOCS-3 is an immediate early gene induced by G-CSF to rapidly modulate G-CSFR-mediated signaling. The strong and rapid induction of SOCS-3 mRNA in myeloid cells by G-CSF reported in this study, together with the previously reported potent induction of SOCS-3 by G-CSF, GM-CSF, and IL-3 in bone marrow cells (22), is a strong indication for SOCS-3 being an important regulator of signal transduction in immune cells.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, activation of AKT was observed predominantly at the late phase and continued for 14 days following TAC. SOCS3 mRNA and protein is induced in the heart by in vivo infusion of gp130 cytokines (23). In addition, recent studies have revealed that the SOCS3 promoter contains a functionally important STAT-binding element (21).…”
Section: Resultsmentioning
confidence: 99%
“…Functionally, CIS and SOCS1-3 proteins interact with cytokine receptors and/or JAKs, thereby inhibiting activation of kinases and STATs. SOCS3 is induced by a variety of cytokines, including CT-1 and LIF (21)(22)(23). SOCS3 binds to JAKs via cytokine receptor, thereby inhibiting the cytokine receptor signaling (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between STAT3 and ERK1/2 in CT-1-induced signaling contributes to development of cardiac hypertrophy 31,87,89 . New fi ndings also indicate that the major pathway responsible for the hypertrophic responses to CT-1 is not JAK-STAT3 pathway nor MEK1-ERK1/2 pathway, but MEK5-ERK5 pathway 49,90 . In vivo, the death of ventricular myocytes leads to heart failure, and downregulation of survival signals and/or augmentation of pro-apoptotic signals are likely to be important components of disease processes.…”
Section: Ct-1 Signallingmentioning
confidence: 89%